Kinnow Peel Candy: Waste Utilization - Chamroy, T; Rawat, Monisha; Mashkey, Vinay Kumar (Indian Horticulture, 2024)
The waste utilization and disposal of fruit processing industries has become one of the biggest challenges faced in the recent past due to the increasing production and processing of fruits and vegetables and plant material being prone to microbial spoilage which is limiting further exploitation. Thus, an attempt to utilize waste products from Kinnow Peel to develop a candy was found necessary in Punjab regions where Kinnow is grown extensively and available in abundance during the main season to minimize the extent of post-harvest losses and add value to the fruit.